2020
DOI: 10.1002/er.5408
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic performance evaluation of the CO 2 parallel compression supermarket refrigeration system with a subcooler

Abstract: Summary Commercial refrigeration systems in supermarkets are intensive users of energy and CO2 is recognized as the most promising refrigerant such systems. The CO2 parallel compression system has been considered in medium‐ and low‐temperature supermarket refrigeration systems, with auxiliary compressors to enhance system performance. This study is intended to investigate the effects of adding a subcooler in a CO2 trans‐critical supermarket refrigeration system with parallel compression (SPR system). Mathemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Astrain et al 35 obtained a 24% amendment of COP by utilizing a multimodule thermoelectric contrivance as a subcooler. Wang et al 36 tested a parallel compression system using a subcooler in different Chinese cities and reported 6.8% energy efficiency promotion. Aranguren et al 37 experimented on thermoelectric subcooling and found an increase in COP of 11.3% and cooling capacity of 15.3%.…”
Section: Introductionmentioning
confidence: 99%
“…Astrain et al 35 obtained a 24% amendment of COP by utilizing a multimodule thermoelectric contrivance as a subcooler. Wang et al 36 tested a parallel compression system using a subcooler in different Chinese cities and reported 6.8% energy efficiency promotion. Aranguren et al 37 experimented on thermoelectric subcooling and found an increase in COP of 11.3% and cooling capacity of 15.3%.…”
Section: Introductionmentioning
confidence: 99%